Religious Moderation and Basic Rights in Education According to Islamic Perspective - Ummi Hanifaa; Meyniar Albina (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Religious moderation is a significant concept in Islam that emphasizes balance, tolerance, and justice, particularly within inclusive education contexts. This article aims to highlight the role of religious moderation in ensuring the fulfillment of basic educational rights for students from diverse cultural and religious backgrounds. Using a literature review method, the article analyzes religious moderation as an approach to creating a fair and harmonious educational environment. The study’s findings show that implementing the principles of moderation in Islamic education not only reduces discrimination but also fosters respect for diversity, which is essential for building a peaceful society. This moderation concept underscores that every student has the right to equal access, participation, and protection within educational settings